The Effect of Profitability and Capital Structure on Stock Prices with Firm Value as an Intervening Variable in LQ45 Companies Listed on the IDX in 2018-2021 - Suhariyanto; Sumaryo (LPPM STIE PPI, 2025)
Introduction/Main Objectives: This study aims to examine the effect of Profitability and Capital Structure on Stock Prices with Firm Value as an Intervening Variable in LQ45 Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. Background Problems: There is uncertainty regarding the fundamental factors that influence stock prices, which shows inconsistent findings, especially regarding the influence of profitability and capital structure. Novelty: This study offers novelty by examining a different unit of analysis and time period compared to previous research and by incorporating a moderating variable. Research Methods: Using quantitative methods with secondary data from financial statements with samples carried out by purposive sampling and data analysis was carried out using multiple linear regression with the help of SPSS software. Finding/Results: Profitability has a significant effect on firm value, while capital structure does not. Profitability, capital structure, and firm value do not have a significant effect on stock prices. Firm value is also unable to mediate the effect of profitability or capital structure on stock prices. Conclusion: These findings indicate that it is better to assess financial statements from various aspects, not only from profitability and capital structure, in order to obtain a more accurate picture of the company's prospects